Performance analysis of inserted resonators in microstrip array antenna for biomedical applications - Man, Cing Nuam; Win, Thanda; Tun, Hla Myo; Aye, Mya Mya (Researcher and Lecturer Society, 2025)
This paper investigates the use of inserted resonators in designing microstrip patch array antenna for biomedical applications, such as respiratory rate detection. The purpose of this study is to analyze size and placement of resonator, and slots which influence the overall performance. The antenna was constructed by connecting two single microstrip patch antennas (11.7mm × 15.7 mm×1.6 mm) on an FR4 substrate with a dielectric constant (????r = 4.4) to form (26 mm × 50mm × 1.6 mm). It achieves a miniaturized design of the expected resonance frequency with directional polarization, and provides good gain and bandwidth. The simulations were operated using FEKO software. The results and size of antenna were compared with references designs. The antenna was also designed for a 5-6 GHz frequency range, making it suitable for ISM band (Industrial, Medical, and Science) band range, low-power wireless applications, including Wi-Fi, and Bluetooth, as well as robotic systems, low-noise amplifier (LNA), 5 G applications, and WiFi 6E standard applications.